Feliks Dzierżyński and the SDKPiL : a study of the origins of Polish communism. - Blobaum, Robert (Boulder, Colorado : East European Monographs, 1984)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Dzierzynski, Feliks; communisme; Polen